Leaching of a Cu-Co ore from Congo using sulphuric acidhydrogen peroxide leachants - Seo S.Y.; Choi W.S.; Kim M.J.; Tran T. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A Cu-Co ore from Katinga Province, the Republic of Congo containing 1.5% Co and 1.6% Cu was tested to determine the leachability of Cu and Co using sulphuric acid and hydrogen peroxide mixtures at different conditions. Without hydrogen peroxide, the maximum extraction of copper and cobalt were found to be ~80% and ~15%, respectively when the acid concentration was varied between 0.36 - 1.1M. When hydrogen peroxide was added (0.008-0.042M), Cu recovery was enhanced to ~90%. Recoveries of ~90% of Co could be achieved at 20ºC, using leachants consisting of 0.36M sulphuric acid and 0.025M hydrogen peroxide after 3 hours. The reaction time to reach 90% Co extraction was reduced to less than 2 hours at 30ºC. Stabcal modelling of the Eh-pH diagrams shows the importance of hydrogen peroxide as a reductant. The decrease of solution potential (300-350 mV) by adding hydrogen peroxide was confirmed by Eh measurements during the tests. The leaching follows the shrinking core model kinetics, where the rate constant is linearly dependent on hydrogen peroxide concentration in the range 0-0.025M and proportional to (1/r2) where r is the average radius of the mineral particles. The activation energy for the leaching process is 72.3 kJ/mol.